DEVELOPMENT OF SOFTWARE FOR IDENTIFICATION OF FILAMENTS USED IN 3D PRINTING TECHNOLOGY - KORGA, Sylwester; BARSZCZ, Marcin; DZIEDZIC, Krzysztof (Applied Computer Science, 2019)
The aim of the work was to develop a computer program that allows identification of polymer materials that are used in 3D printing technology. The computer program was made using the algorithm that concerns the method of thermal polymer degradation. Filament samples were prepared for this purpose and then set on fire. The collected data on the flammability of polymers was used in an algorithm that can make a decision to identify the name of the polymer. The software can be used to identify polymer prints used for 3D printing technology. The computer program supports the process of recycling plastics and supports ecological work.